La eficiencia de las residencias de mayores: Propuesta de medición y resultados en la provincia de Zaragoza - Manuel Carreras Lecina; Lucía Isabel García Cebrián (Atlantic Review of Economics, 2016)
– This paper calculates the efficiency of senior residences in Saragossa and province by means of the Data Envelopment Analysis (DEA). The study of the efficiency has been divided in two stages: in the first one the efficiency of the productive system of senior residences is calculated and analyzed, and in the second one, the relation between efficiency and the quality in the service provided by residences. Results show a lack of positive correlation among these two variables. The aim of this paper is not only to analyze efficiency in residences located in Saragossa, but also to provide a methodology easy and useful for evaluating the service offered by this type of organizations.
Keywords: C61; J14; L15; I38; 330; efficiency; Data Envelopment Analysis; senior residences; Welfare State